2014
DOI: 10.2147/clep.s73662
|View full text |Cite
|
Sign up to set email alerts
|

Parental celiac disease and risk of asthma in offspring: a Danish nationwide cohort study

Abstract: ObjectiveThe incidences of celiac disease (CD) and asthma are increasing and the two conditions are associated in individuals. Risk of asthma may be passed on to the next generation through shared risk factors. We examined whether parental CD is associated with risk of asthma in offspring.MethodsWe conducted a population-based Danish nationwide cohort study, using medical databases, covering the period 1 January 1979 to 31 December 2009. For each child with a parental history of CD, we randomly sampled 100 chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…On the other hand, Kero et al (25) reported a cumulative incidence of asthma in children with CD (24.6%) significantly higher than in children without CD (3.4%; P<0.001) and Ress et al (26) showed that CD prevalence in children with active atopic dermatitis was more than four times as high as in randomly selected children. Some studies have suggested that the association between CD (T-helper cell type 1 disease) and atopy (T-helper cell type 2 disease) may be the result of vitamin D deficiency and subsequently insufficient Treg-cell capacity and shared risk factors (27,28) .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Kero et al (25) reported a cumulative incidence of asthma in children with CD (24.6%) significantly higher than in children without CD (3.4%; P<0.001) and Ress et al (26) showed that CD prevalence in children with active atopic dermatitis was more than four times as high as in randomly selected children. Some studies have suggested that the association between CD (T-helper cell type 1 disease) and atopy (T-helper cell type 2 disease) may be the result of vitamin D deficiency and subsequently insufficient Treg-cell capacity and shared risk factors (27,28) .…”
Section: Discussionmentioning
confidence: 99%
“…5 cannot be completely excluded (31,32). A cohort study that examined the association between CD and asthma from a different perspective found no increased risk of asthma in the children of parents diagnosed with CD (33). A different case-control study conducted in Italy concluded that CD is not associated with atopy (34).…”
mentioning
confidence: 99%